2009
DOI: 10.7326/0003-4819-151-7-200910060-00009
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein as a Risk Factor for Coronary Heart Disease: A Systematic Review and Meta-analyses for the U.S. Preventive Services Task Force

Abstract: Strong evidence indicates that CRP is associated with CHD events. Moderate, consistent evidence suggests that adding CRP to risk prediction models among initially intermediate-risk persons improves risk stratification. However, sufficient evidence that reducing CRP levels prevents CHD events is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
353
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 476 publications
(371 citation statements)
references
References 98 publications
7
353
0
11
Order By: Relevance
“…Serum CRP levels are well studied as sensitive circulating markers of inflammation, as CRP is independently associated with an increased risk of cardiovascular disease and diabetes (18)(19)(20)(21)(22). In addition to these previous associations, our study identifies new information regarding CRP and disease outcomes.…”
Section: Discussionmentioning
confidence: 67%
“…Serum CRP levels are well studied as sensitive circulating markers of inflammation, as CRP is independently associated with an increased risk of cardiovascular disease and diabetes (18)(19)(20)(21)(22). In addition to these previous associations, our study identifies new information regarding CRP and disease outcomes.…”
Section: Discussionmentioning
confidence: 67%
“…The participants categorised into the Low PA group according to the IPAQ-E had a mean hs-CRP .3 mg/l. In clinical practice, hs-CRP .3 mg/l is classified as indicating a high risk for a cardiac event (28,29) . This suggests that the IPAQ-E was able to indicate participants having this risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…While it is clear that minor CRP level elevation is associated with a moderately increased relative risk of future myocardial infarction (18,19), many studies have shown that CRP determination adds little to a thorough evaluation of known risk factors (12,20,21). Risk factors are merely epidemiologically determined associations.…”
Section: Why Does Minor Crp Level Elevation Predict Coronary Events?mentioning
confidence: 99%